The role of trachelectomy in cervical cancer - Halaska, Mj; Robova, H; Pluta, M; Rob, L (Ecancermedicalscience, 2015)
Cervical cancer is one of the most common cancers in women worldwide. Because it often affects women of childbearing age (19-45 years), fertility-sparing surgery is an important issue. The article reviews current viable fertility-sparing options with a special focus on trachelectomy, including vaginal radical trachelectomy, abdominal radical trachelectomy and simple trachelectomy. Neoadjuvant chemotherapy is also discussed. Finally, the decision to proceed with fertility-sparing treatment should be a patient-driven process.
Keywords: trachelectomy; chemotherapy; cervical cancer; pregnancy outcome